Степан Шаумян на позициях решения общенациональных задач в1917-1918 гг. - Меликян, Ваан (ՀՀ ԳԱԱ Պատմության ինստիտուտ)
After the Bolshevik coup of 1917, on November 15, a new body of power was formed in Tiflis, the Transcaucasian Commissariat, which did not recognize the Soviet power of Russia. As a demonstration of an alternative to the government, the body of the Soviet government operating in Baku the council with the SR-Menshevik majority under the chairmanship of the Bolshevik St. Shahumyan, embarked on the implementation of the program of Sovietization of the region in two stages (November 1917 and February-March 1918). There was a significant contradiction: on the one hand, the government defending the values of the February revolution of 1917 on behalf of the socialist parties of the commissariat, did not accept and was hostile to the victory of Bolshevism, which led the region to secession from Russia, on the other hand, the Georgian-Tatar agreement formed against Armenians and its influential political forces clearly carried out a plan to weaken the Armenian element in Transcaucasia. In addition to that Turkey intruded into Transcaucasia in 1918 which contributed to the isolation of the ARF within the Commissariat and then the Seim. St. Shahumyan was trying to oppose his plan to that big anti-Armenian alliance, which has a national character in that difficult and fatal historical stage. Accordingly, it was planned to put an end to the antiRussian and anti-Armenian riots in Baku and then the Yerevan province with the forces of the national military units subordinate to the Baku Council, and then to protect Western Armenia with the support of the Bolshevized military units (only Sarighamish garrison had 30,000 soldiers who were waiting for St. Shahumyan’s order to capture Tiflis) of the Caucasian Army. The Soviet Decree “On Turkish Armenia” published on December 29, 1917 was circulated in this context. The nationwide nature of St. Shahumyan’s plan is evidenced by the defense of Baku in March 1918, where the exceptionally far-sighted cooperation of national and Bolshevik figures (Rostom, General H. Bagratuni, Hamazasp, St. Shahumyan and others) defeated the first Musavat attempt to capture Baku.
Keywords: История